Private post-secondary library websites and the ADA: compliancy and COVID-19 - Bielefield, Arlene; Liu, Yan Quan; Waimon, Victoria (Universal Access in the Information Society, 2023)
This study explores whether US post-secondary institutions (PPI) follow philosophies to foster inclusive communities, providing resources for those individuals with disabilities thrive socially, personally, and academically, while there have been no thorough studies conducted to determine web accessibility of the nation’s top-ranked PPI library webpages. Additionally, this study pioneers in comparison with the accessibility of PPI’s library homepages fighting COVID-19. The study evaluated the library homepages of the premium PPIs based on Money.com’s 2019 list of “The Best Colleges in America” via the WAVE web accessibility evaluation tool. The outcomes determined that most of the library homepages analyzed were littered with numerous errors, and the shift to online-based research in learning had no significant impact on the number of errors WAVE detected. The disconcerting findings of this study demonstrate the overall failure to recognize the importance of web accessibility or perhaps even the indifference toward accessibility on the part of the PPI community.
Keywords: ADA; Academic libraries; Accessibility; COVID-19; Disability; Overall failure; Philosophical aspects; Post-secondary institutions; Private colleges and universities; SCSU-student; Section 508; WAVE; WCAG; Web accessibility; Websites; dept.ils; peer-reviewed

Academic pursuits and involvement in decision-making: study on the formation of U.S. university think tanks - Lyu, Qing; Bielefield, Arlene; Liu, Yan Quan (Administrative Sciences, 2023)
This paper analyzes the concept of think tanks and concludes that think tanks have three basic characteristics. Firstly, they are based on academic research, relatively independent operation, and aim to serve scientific decision-making. Taking Ivy League think tanks as an example, this paper provides a preliminary discussion of ways for think tanks to maintain the scientific nature of their research, maintain the independence of their operations, and disseminate research results to enhance their influence. It covers institutional mission, research team construction, institutional governance, fundraising, achievements and activities, and alumni networks. This paper proposes a framework of university think tank generation paths associated with the essential characteristics of think tanks. The paper points out that, as a research consulting organization grown out of universities, university think tanks must maintain the scientific nature and independence of research while providing support and services for decision-making. Only in this way can they truly serve scientific and democratic decision-making, gain the trust of the public and have a real lasting influence.
0 citations (Crossref) [2023-10-31] Number: 3
Keywords: American university affiliated think tank; characteristics of think tank; decision-making; dept.ils; peer-reviewed; the ivy league university; think tank operation mechanism

ADA digital accessibility on academic library websites - Liu, Yan Quan; Bielefield, Arlene; Beckwith, Jennifer (College & Research Libraries, 2024)
Studying ADA accessibility at library websites of top universities selected from the U.S. News and World Report, the authors used WAVE and AChecker to assess data in compliance with WCAG 2.0 standards. Almost 8 out of 10 public university academic libraries reported accessibility errors as one of the major findings. Low color contrast was becoming a more commonly occurring accessibility issue, making it difficult for people with vision impairments to perceive the color of the image. The outcomes of the study suggest that academic libraries around the world should continue improving their website accessibility.
Keywords: SCSU-student; dept.ils; peer-reviewed

Are Ivy League libraries’ websites ADA compliant? - Yang, Wenfan; Zhao, Bin; Liu, Yan Quan; Bielefield, Arlene (Information Technology and Libraries, 2020)
As a doorway for users seeking information, library websites should be accessible to all, including those who are visually or physically impaired and those with reading or learning disabilities. In conjunction with an earlier study, this paper presents a comparative evaluation of Ivy League university library homepages with regard to the Americans with Disabilities Act (ADA) mandates. Data results from WAVE and AChecker evaluations indicate that although the error of Missing Form Labels still occurs in these websites, other known accessibility errors and issues have been significantly improved from five years ago.
3 citations (Crossref) [2023-10-31]
Keywords: dept.ils; peer-reviewed

The provision of patron services in Chinese academic libraries responding to the COVID-19 pandemic - Guo, Yajun; Yang, Zinan; Yang, Zhishun; Liu, Yan Quan; Bielefield, Arlene; Tharp, Gregory (Library Hi Tech, 2020)
Purpose: The purpose of this paper is to identify the measures employed in the provision of patron services in Chinese academic libraries responding to the COVID-19 pandemic, noting the challenges and issues inherent in providing substantial services while undergoing a public health emergency. Design/methodology/approach: This paper uses an analytical survey study of 137 Chinese academic libraries using data collected through a combination of website investigation, social media access and direct correspondences. Findings: Over 94% of Chinese academic libraries released COVID-19-related information through their websites; the majority switched their service focus to partly or solely remotely online, including remote access, free electronic resources, virtual references reachable 24/7 and research support services deliverable online; services of print materials were altered to e-books for conveniences. Research limitations/implications: It should be noted that the survey was conducted from February 12 to April 5, 2020; because of the rapid updates to the library's website and social media channels, the status of their patron services are in the process of dynamic changes and that there should be many libraries that have adopted some patron service methods, but this study is difficult to cover comprehensively. In addition, patron services carried out offline by the surveyed libraries but not disclosed on the online platform could not be analyzed in a way that would be consistent with the data provided by the survey. Originality/value: By providing evidence of the current status of patron services in Chinese academic libraries during the COVID-19 pandemic, this study helps fulfill the scant empirical attention given to the impact of nationwide public health crises on academic libraries and offers new data of the best practices that help library administrators enhance the impact, efficiency and value of library services to their target community users. © 2020, Emerald Publishing Limited.
32 citations (Crossref) [2023-10-31] tex.ids: guoProvisionPatronServices2020a tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85088570958 type: Article
Keywords: Academic libraries; COVID-19; China; Patron services; Survey; Virtual services; dept.ils; peer-reviewed